The current state of degradation, pollution of groundwater in Quaternary sediments in the Thai Binh province - Tam, Le Thi Thanh; Phong, Dang Xuan; Dung, Truong Phuong (Vietnam Journal of Earth Sciences, 2014)
The Thai Binh province has 3 aquifers in Quaternary sediments, including Aquifer qh1 is completely salty but aquifer qh2 and qp are divided from the poor to the rich of groundwater storage level and savory faintly no rule. The main product is qp aquifer where was and is being exploited and used by communities. Groundwater reserves in the province, according to the master plan for the socio-economic development of the province until 2020, that groundwater in Quaternary sediments are not enough to provide for local needs.Over the years, the groundwater has been showing signs of contamination by metals such as Mn, Fe, some places are As phenomenal especially contamination by organic substances such as COD, P3O4 3 NO2 and pathogenic bacteria. In coastal areas, the phenomenon of the salty water layer has become more pronounced. Besides, there is the phenomenon of lowering the water level of the water layer reports in the region.All of these phenomena on the apparent warning to the verge of recession groundwater source. There are many causes of degradation in the groundwater source, there are natural and artificial causes due to production and living of the community. To protect groundwater in local research needs planning and rational use of this resource in the future.